Exit Strategy: An Exploration of Late-Stage Police Crime - Freiburger, Tina L. (2010)
There are no exhaustive statistics available on the crimes committed by law enforcement officers, and only a small number of studies provide specific data on police crimes. The purpose of the current study is to examine the character of police arrests known to the media. Cases were identified through a content analysis of news coverage using the internet-based GoogleTM News search engine and its Google News Alerts search tool. The study focuses on the crimes committed by experienced officers who are approaching retirement. The occurrence of these late-stage crimes presents a challenge to existing assumptions regarding the relationship between experience and various forms of police misconduct, and also provides an opportunity to examine a stage of the police career that has not been the subject of much research. The paper concludes with an identification of research and policy implications, and includes a discussion regarding how our data should be interpreted within the context of existing studies on police socialization and the production of misconduct